Preference of Rural Youth Livelihood in Indonesia Rural Areas and Its Factors - Anisa Aprilia; Condro Puspo Nugroho; Rini Mutisari (HABITAT, 2019)
Indonesia is facing serious problem of unemployment in rural areas while in agricultural sector, there is lack of labour availability. This research discusses issue between livelihood choices and their determinant factors of rural youth in East Java, Indonesia. The 200 survey data was analysed by multinomial logit for measuring response probabilities of alternative livelihoods which consist of agricultural jobs, non-agricultural employment, non-farm entrepreneur, and urban employment. The outcome of the research is that education of youth has consistently positive and significant correlation with livelihood option which is outside of agricultural sector. The more academic achievements that respondents get, the more reasonable their expectation of success in outside farming relative to agriculture. On the other hand, the larger land holding that their parents have, the lower possibility in choosing a livelihood outside of agriculture over farming. Therefore, it implies that better land access will encourages youth to approach agricultural works.